2018
DOI: 10.3389/fphar.2018.00233
|View full text |Cite
|
Sign up to set email alerts
|

Time and Concentration Dependent Effects of Short Chain Fatty Acids on Lipopolysaccharide- or Tumor Necrosis Factor α-Induced Endothelial Activation

Abstract: Background and Aim: Endothelial activation is characterized by excessive production of cytokines and chemokines as well as adhesion molecules expression which is involved in the development of atherosclerosis. The aim of our study is to investigate the effects of short chain fatty acids (SCFA) on lipopolysaccharide (LPS) or tumor necrosis factor alpha (TNFα)-induced endothelial activation.Methods and Results: Human umbilical vein endothelial cells (HUVEC) were pre-treated with acetate (10 mM), butyrate (0.1 mM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 37 publications
4
50
0
1
Order By: Relevance
“…SCFAs also exert direct protective effect in the endothelium by decreasing endothelial activation induced by LPS or TNFα. 59,60 We found that acetate plasma levels in DOCA-salt rats were similar to control, despite higher proportion of acetate-producing bacteria. This may be linked to the reduced levels of SCFA transporters (MCT1 and MCT4) expressed in gut from DOCA rats.…”
Section: Discussionmentioning
confidence: 65%
“…SCFAs also exert direct protective effect in the endothelium by decreasing endothelial activation induced by LPS or TNFα. 59,60 We found that acetate plasma levels in DOCA-salt rats were similar to control, despite higher proportion of acetate-producing bacteria. This may be linked to the reduced levels of SCFA transporters (MCT1 and MCT4) expressed in gut from DOCA rats.…”
Section: Discussionmentioning
confidence: 65%
“…To determine whether GPR41/43 are involved in the decrease of IL-6 and IL-8 production by acetate, we compared the effects of acetate alone or in combination with antagonists of GPR41/43. Optimum concentrations and incubation times for SCFA and LPS/TNFα were determined previously ( Li et al, 2018 ). Acetate treatment alone showed no significant effects on IL-6 and IL-8 production compared to the control group (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Based on previous experiments ( Li et al, 2018 ), propionate (10 mM), butyrate (5 mM), and TSA (1 μM), either alone or in combination with antagonists, were used to pretreat confluent HUVEC for 24 h and then exposed to TNFα (1 ng/mL) for 8 h. TNFα increased the VCAM-1 expression ( Figure 5 ). Butyrate, propionate and TSA all inhibited TNFα-induced VCAM-1 expression, and the effect was not reversed by GLPG and/or SHB treatment ( Figures 5A,B ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations